2019
DOI: 10.5430/jnep.v9n7p18
|View full text |Cite
|
Sign up to set email alerts
|

The effect of emotional intelligence intervention on nursing students’ practice and patients’ clinical outcomes at burn intensive care unit

Abstract: Background and objective: Emotional intelligence in nursing practice helps students better deal with clinical pressures and communicates effectively with patients. Therefore, developing students' emotional maturity may seem more important than their physical responsibilities. The current study was carried out to evaluate the effect of emotional intelligence intervention on nursing students’ practice and their reflections on patients’ clinical outcomes at burn intensive care unit.Methods: This study was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Nursing students that exhibit EI in their work are better able to manage pressure from their patients and interact with them. 25 Data from our study revealed that the mean EI scores were higher in the area of emotional regulation (51.1 ± 6.95) and low in the area of self-motivation (32.41 ± 4.89). Overall mean of EI score was 254.35 (maximum possible score being 354 and higher score indicating higher EI).…”
Section: Discussionmentioning
confidence: 51%
“…Nursing students that exhibit EI in their work are better able to manage pressure from their patients and interact with them. 25 Data from our study revealed that the mean EI scores were higher in the area of emotional regulation (51.1 ± 6.95) and low in the area of self-motivation (32.41 ± 4.89). Overall mean of EI score was 254.35 (maximum possible score being 354 and higher score indicating higher EI).…”
Section: Discussionmentioning
confidence: 51%